2020
DOI: 10.1002/lsm.23246
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical Ablation‐Assisted Photodynamic Therapy for the Treatment of Acne Vulgaris. A Retrospective Chart Review of 30 Patients

Abstract: Background and Objectives Acne vulgaris, a chronic inflammatory disease, affects more than 90% of teenagers. The first‐line treatments for acne vulgaris are topical and oral medications, mainly antibiotics and retinoids. However, antibiotic resistance of Propionibacterium acnes, contraindications, partial response, significant adverse effects, or recurrence creates demand for novel treatment options in acne. Aminolevulinic acid (ALA) photodynamic therapy (PDT) is a well‐established modality in the treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Red light is the most widely used light source for PDT. In some small studies, several laser and light devices can additionally be used safely prior to PDT [116][117][118]. One retrospective chart review of 30 patients suggests thermomechanical ablation before ALA-PDT may enhance its efficacy in treating acne [116].…”
Section: Photodynamic Therapy (Pdt)mentioning
confidence: 99%
See 1 more Smart Citation
“…Red light is the most widely used light source for PDT. In some small studies, several laser and light devices can additionally be used safely prior to PDT [116][117][118]. One retrospective chart review of 30 patients suggests thermomechanical ablation before ALA-PDT may enhance its efficacy in treating acne [116].…”
Section: Photodynamic Therapy (Pdt)mentioning
confidence: 99%
“…In some small studies, several laser and light devices can additionally be used safely prior to PDT [116][117][118]. One retrospective chart review of 30 patients suggests thermomechanical ablation before ALA-PDT may enhance its efficacy in treating acne [116]. A randomized controlled, and rater-blinded trial of ten patients showed that 15 minutes of radiant infrared LED therapy (970 nm) before PDT (median reduction of 73%) was significantly more effective at reducing acne lesions than PDT alone (median reduction of 38%) [118].…”
Section: Photodynamic Therapy (Pdt)mentioning
confidence: 99%
“…It has been previously shown that pulse durations around 6 milliseconds are used for drug delivery and those greater than 10 milliseconds are used for rejuvenation; common settings for rejuvenation are 12-14 milliseconds. 11,25,26 As the periorbital region is a sensitive area, coordinating treatment at two centers in different countries with diverse populations warranted more conservative treatment parameters. The depth was chosen based on the depth of the periorbital skin to the reach the papillary dermis ~300 µm (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we chose a more conservative approach with a pulse duration of 10 milliseconds and 500 µm protrusion. It has been previously shown that pulse durations around 6 milliseconds are used for drug delivery and those greater than 10 milliseconds are used for rejuvenation; common settings for rejuvenation are 12–14 milliseconds 11,25,26 …”
Section: Discussionmentioning
confidence: 99%
“…When Tixel® is used over the exposed dermis, augmented results can be achieved. (4) TMFI-assisted drug delivery: Tixel, known to improve drug delivery [16], has already been utilized in the treatment of several medical conditions, including hypertrophic scars [17], acne [18], and rosacea [19]. Therefore, combining the esthetic thermomechanical effect with different cosmeceutical or drug delivery might augment the results.…”
Section: Discussionmentioning
confidence: 99%